Analisis Struktur Beton Bertulang Gedung PT Astari Niagara Internasional Menggunakan Metode Analisis Pushover Sesuai SNI 1726-2019 - Purnamasari, Endah; Ikhsan, Muhammad Nur; Pradana, Raka Surya (SENTRI: Jurnal Riset Ilmiah, 2026)
The increasing demand for earthquake-resistant buildings requires structural performance evaluation methods that are capable of representing nonlinear behavior under seismic loading. This study aims to analyze the reinforced concrete structure of the Astari Niagara International, Ltd building using the Pushover method in ETABS and to evaluate the development of plastic hinges and the structural response under lateral loading based on SNI 1726:2019. The research employed a three-dimensional structural model with gravity, live, and seismic loads, while nonlinear static (pushover) analysis was performed by assigning plastic hinges to beams and columns. The evaluation referred to ATC-40, FEMA 356/FEMA 440, and Pranata (2006), including the interpretation of capacity curves, displacement response, and plastic hinge distribution. The modal analysis produced 12 vibration modes with a fundamental period of 0.577969 s and an elastic spectral displacement of 54.77 mm. The recorded capacity curves indicated maximum base shears of 16,737.67 kN in the X direction and 16,486.71 kN in the Y direction, while the Y direction exhibited greater displacement, indicating lower lateral stiffness. Plastic hinge development was dominated by the A–B and B–C performance ranges, with only a few hinges progressing to higher damage states. However, the nonlinear analysis did not reach convergence because the Dead Nonlinear case produced 34 null steps and two negative stiffness eigenvalues, resulting in unstable initial conditions for the PUSH X and PUSH Y analyses. Consequently, the capacity curves and plastic hinge distributions are descriptive only and cannot yet be used to determine the performance point, target displacement, ductility, or seismic performance level. Structural model improvement and successful convergence are required before a definitive seismic performance evaluation can be established.